Biogas Science and Technology - Gübitz, Georg; Bauer, Alexander; Bochmann, Guenther; Gronauer, Andreas; Weiss, Stefan (Advances in Biochemical Engineering/Biotechnology, 2015)
Michael Lebuhn, Stefan Weiß, Bernhard Munk, Georg M. Guebitz Microbiology and Molecular Biology Tools for Biogas Process Analysis, Diagnosis and Control Veronika Dollhofer, Sabine Marie Podmirseg, Tony Martin Callaghan, Gareth Wyn Griffith & Katerina Fliegerová Anaerobic Fungi and their Potential for Biogas Production Bianca Fröschle, Monika Heiermann, Michael Lebuhn, Ute Messelhäusser, Matthias Plöchl Hygiene and Sanitation in Biogas Plants Charles-David Dubé and Serge R. Guiot Direct Interspecies Electron Transfer in Anaerobic Digestion: A Review Simon K.-M. R. Rittmann A Critical Assessment of Microbiological Biogas to Biomethane Upgrading Systems Manfred Lübken, Pascal Kosse, Konrad Koch, Tito Gehring, Marc Wichern Influent Fractionation for Modeling Continuous Anaerobic Digestion Processes Fermoso, F. G, van Hullebusch, E. D, Guibaud, G, Collins, G,  Svensson, B. H, Carliell-Marquet, C, Vink, J.P.M,  Esposito, G,  Frunzo, L Fate of Trace Metals in Anaerobic Digestion.